Kampanye dan Perilaku Memilih di Indonesia Studi Kasus Pemilihan Umum 2019 Dapil Jawa Timur 11 dan Dapil 7 Sulawesi Selatan - Andi Yusuf Akbar; Fatma Hidayah; Udyahitani Secundaputeri (Syntax Corporation, 2023)
The nature of democracy aims to present an organized government to realize the individual rights of citizens, so that an open proportional electoral system allows compulsory voting in democratic parties including choosing legislative candidates. In a more complex multi-party system such as in Indonesia, political parties are encouraged to be able to carefully understand the behavior of voters who sociologically and psychologically determine their political orientation not based on party identification but on the individual's leadership. Through this research, it is known that the quality of candidates' shops is based on endorsements or support from central figures in a constituency. From the perspective of symbolic convergence, it can be concluded that when campaigning, the basic message that is the main force of a political party today is about the ability of its cadres both in the region and in the center, the cadre in question can be from the class of legislative candidates or the Chairman of the party, which is then validated by regional figures. That issue is reflected in the success of Willy Aditya and Andi Izmand Maulana Padjalangi winning the 2019 elections, so the theory of symbolic convergence can be scientifically used as a reference for drafting campaign strategies.